Insights into the catalytic oxidation of toluene over CoO -based catalysts: A review - Ye, Dong; Feng, Jingyi; Gao, Shujie; Wang, Xiaoxiang; Zhu, Kai; Wu, Ke; Guo, Ruitang (Journal of industrial and engineering chemistry (Seoul, Korea), 2025)
Volatile organic compounds (VOCs) are significant contributors to air pollution, presenting substantial risks to both environmental health and human well-being. Toluene, a prevalent VOC, is commonly employed as a model compound in laboratory studies due to its widespread occurrence across various industrial sectors. Catalytic oxidation has emerged as a highly effective method for removing toluene from exhaust gases. Among various catalytic materials, cobalt oxides (CoOx) have garnered increasing attention for their potential as active species and additives in toluene degradation, owing to their ease of synthesis and cost-effectiveness. This review sum- marizes recent developments in the catalytic oxidation of toluene using CoO -based catalysts. Key properties,xsuch as catalytic activity, CO2 selectivity, and the adaptability to flue gas components, are identified as crucial factors for assessing catalyst performance in practical applications. Approaches to enhance these properties are discussed, alongside a comprehensive analysis of the reaction mechanisms, providing valuable insights from a microscopic perspective. In conclusion, the review underscores the importance of developing novel catalysts that can stably and efficiently eliminate toluene from exhaust gases. KCI Citation Count: 0